Rancang Bangun Manajemen Bimbingan Tugas Akhir Pada Jurusan Teknik Industri Universitas Muhammadiyah Malang - Aristy Indana; Wildan Suharso; Shanty Kusuma Dewi (Universitas Muhammadiyah Malang, 2020)
The final assignment is a scientific paper, in the form of writing research results that must be completed by each student to get a bachelor's degree. In the Department of Industrial Engineering there are several stages of the process that must be done by students, including registration of supervisors, seminar proposals and final hearings. So far the registration is still using google form where it is only limited to registration, and for the final assignment guidance report has not been recorded properly and done manually using the assistance sheet in the thesis logbook so the final assignment supervisor and coordinator has difficulty monitoring the student's guidance. The purpose of this study is to build a website-based system using the codeigniter framework and the waterfall method. The stages passed in the waterfall method include needs analysis, system design, implementation and system testing. The results of this research are the final assignment guidance management system in the industrial engineering department of Muhammadiyah Malang University which can monitor, assist in reporting guidance activities, and registration in the final assignment process.The final assignment is a scientific paper, in the form of writing research results that must be completed by each student to get a bachelor's degree. In the Department of Industrial Engineering there are several stages of the process that must be done by students, including registration of supervisors, seminar proposals and final hearings. So far the registration is still using google form where it is only limited to registration, and for the final assignment guidance report has not been recorded properly and done manually using the assistance sheet in the thesis logbook so the final assignment supervisor and coordinator has difficulty monitoring the student's guidance. The purpose of this study is to build a website-based system using the codeigniter framework and the waterfall method. The stages passed in the waterfall method include needs analysis, system design, implementation and system testing. The results of this research are the final assignment guidance management system in the industrial engineering department of Muhammadiyah Malang University which can monitor, assist in reporting guidance activities, and registration in the final assignment process.